Effect of negative pressure therapy on the treatment response to scar thickness and viscoelasticity - Shen, Wei-Cheng; Cheng, Hsu-Tang; Jan, Yih-Kuen; Liau, Ben-Yi; Hsieh, Chang-Wei; Bau, Jian-Guo; Tai, Chien-Cheng; Lung, Chi-Wen (Frontiers in Bioengineering and Biotechnology, 2024)
Patients with scars face a grave threat to their mental and physical health. Negative pressure has been used for scar therapy in medical care and provides a microenvironment conducive to scar healing while stimulating cell regeneration. Negative pressure may disrupt scar tissue regeneration when it is too high or too low, so finding a suitable negative pressure is important. We hypothesized that different negative pressure magnitudes would affect scar tissue properties differently. This research aimed to provide practical recommendations for scar therapy. This study used three negative pressures (-105 mmHg, -125 mmHg, and -145 mmHg) to compare scar material properties. We measured scar tissue thickness and viscoelasticity with a motor-driven ultrasound indentation system. According to the results of this study, scar thickness is most effectively reduced at a negative pressure of -105 mmHg. In comparison, scar viscoelasticity continuously increases at a negative pressure of -125 mmHg. The negative pressure therapy can be recommended to scar care clinics based on the results of this study.